Control of power systems and power electronic converters - Foo, Chek Fok (2008)
Methods to model and control large power networks, the applications of power electronic switching devices for power system control, and for the enhancement of power quality are described. As the purpose of the RGM is to fund the training of man-power under these rather wide area, this report will only describe selected aspects of the work, including that of · the determination of power system load model for stability analysis · the control of under-excited generators to prevent stator end-core overheating · the design of dynamic voltage restoration control schemes to enhance power quality · the use of distributed generators in power quality improvement and · the designs of network systems with unbundled power quality supply features. The above areas encompass the applications of modeling techniques based on artificial neural networks, control system design, series and parallel compensation schemes effected through power converters. Furthermore, the use of solid-oxide fuel cells for stationary power generation is also described, for which their role as a form of distributed generation is examined in details.